The Effect of EPub-Assisted Teaching Materials to Improve Students’ Numeracy Ability - Enjang Sadam; Jozua Sabandar; Wahyu Hidayat ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
Numeracy ability has increasingly been recognized as a fundamental competence necessary for students to engage meaningfully with mathematics and real-world problem solving. However, many schools still struggle to cultivate strong numeracy due to the limited use of effective and innovative learning materials. This study aims to examine the effectiveness of EPUB-assisted teaching materials integrated with the MERRDEKA (Mulai dari diri, Eksplorasi konsep, Refleksi mandiri, Ruang kolaborasi, Demonstrasi, Elaborasi, Koneksi materi, dan Aksi nyata) learning flow in improving students numeracy ability. A quasi-experimental method was employed using a pretest-postest control group design. The participants consisted of students from classes XI-C and XI-D, totaling 72 students. Data were collected using a numeracy test as the primary quantitative instrument. The analysis involved calculating N-Gain scores and conducting an independent sample t-test to determine differences in learning improvement between groups. The result showed that the experimental class achieved an N-Gain score of 0.77 (high category), whereas the control class obtained an N-Gain score of 0.45 (medium category). In addition, the independent sample t-test yielded a significance velue of 0.001 < 0.05, indicating a significance difference in numeracy ability improvement between the two groups. Therefore, EPUB-assisted teaching materials integrated with the MERRDEKA learning flow are concluded to be effective in enhancing students numeracy ability.